Experimental study of tool wears to join Al6026 aluminium alloy by Ultrasonic Assisted Friction Stir welding. (2022) - Chowdhury, Ivy; Sengupta, Kaushik; Kumar Maji, Kaustav; Roy, Swapna; Ghosal, Sujit
Abstract: Ultrasonic Assisted Friction Stir Welding is being used in various processes to get enhanced value in the welding properties while reducing the tool wear. Using HSS as tool material, 6026 aluminium base plates has been joined by FSW process and Ultrasonic Assisted Friction Stir Welding. In this experimental study, an attempt has been made to obtain the optimum tool wear values by adjusting the rotational speed, transverse speed and frequency in the range of 400 to 600 rpm, 15 to 25 mm/min and 10 to 14 KHz respectively. This paper investigates the tool wear while joining Al6026 aluminium alloy plates using FSW and UAFSW. The specimen samples have been joined by both FSW and UAFSW process and the tool wear has been studied. The difference in the tool wear has been analysed in both FSW and FSW process and results obtained has been presented to advice the utilisation of the ultrasonic vibration with the FSW process to increase tool life. The suitable vibration that can be used in FSW process has also been studied and presented in the paper. A decrease of 25 % in the tool wear has been observed on using the ultrasonic vibration to FSW, which presented that advantage of the ultrasonic energy in the FSW process for industrial utilisation with increased tool life.